Cooperation and wealth - Oded Stark (Institute for Advanced Studies (IHS), 2002)
We calculate the equilibrium fraction of cooperators in a population in which payoffs accrue from playing a single-shot prisoner's dilemma game. Individuals who are hardwired as cooperators or defectors are randomly matched into pairs, and cooperators are able to perfectly find out the type of a partner to a game by incurring a recognition cost. We show that the equilibrium fraction of cooperators relates negatively to the population's level of wealth.
Keywords: A13; C70; 330; equilibrium fraction of cooperators; population's level of wealth; single-shot prisoner's dilemma game; Gefangenendilemma; Kooperatives Spiel; Vermögen; Theorie